2002
DOI: 10.1177/03635465020300040801
|View full text |Cite
|
Sign up to set email alerts
|

A Biomechanical Analysis of Meniscal Repair Techniques

Abstract: Knowledge of biomechanical characteristics aids the surgeon in choosing the appropriate technique for each situation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
1
6

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(71 citation statements)
references
References 24 publications
(27 reference statements)
3
61
1
6
Order By: Relevance
“…The higher pullout strength of vertical sutures found in this study is consistent with findings of various previous studies. 5,9,[11][12][13][14]19,29,35,37,44 In accordance with other studies, the pullout strength of rigid meniscus anchors (10-mm Meniscus Arrow, 48.8 ± 1.1 N) was inferior to vertical and horizontal suture repair, but there was no significant difference from the flexible RapidLoc repair system (45.2 ± 1.4 N). AlbrechtOlsen et al 3 reported a mean pullout strength of 53 N (range, 42-65 N) for the 13-mm Meniscus Arrow in a bovine model; Arnoczky and Lavagnino 5 found a pullout strength of 57.7 ± 13.8 N in a bovine meniscus; and Becker et al 13 reported a pullout strength of 32.7 N using a human model.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The higher pullout strength of vertical sutures found in this study is consistent with findings of various previous studies. 5,9,[11][12][13][14]19,29,35,37,44 In accordance with other studies, the pullout strength of rigid meniscus anchors (10-mm Meniscus Arrow, 48.8 ± 1.1 N) was inferior to vertical and horizontal suture repair, but there was no significant difference from the flexible RapidLoc repair system (45.2 ± 1.4 N). AlbrechtOlsen et al 3 reported a mean pullout strength of 53 N (range, 42-65 N) for the 13-mm Meniscus Arrow in a bovine model; Arnoczky and Lavagnino 5 found a pullout strength of 57.7 ± 13.8 N in a bovine meniscus; and Becker et al 13 reported a pullout strength of 32.7 N using a human model.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, 60 fresh-frozen lateral bovine menisci were used as described by Rankin et al, 37 Boenisch et al, 14 and Arnoczky et al 5,8 The mean age of the animals was 28 weeks ± 2 weeks. Material properties of bovine menisci have been described by Proctor et al 36 The menisci were dissected free, leaving the adhering capsule intact, and stored at -20°C until 5 hours before testing.…”
Section: Biomechanical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…5,9,17,35,78,80,81 Vertical sutures are superior to both horizontal sutures and meniscus arrows in mean load-to-failure values. 4,16,52,78 The superior strength of vertical sutures is hypothesized to be due to the perpendicular orientation to the circumferential collagen bundles of the meniscus. 52 We have previously described the operative techniques for meniscus repair of various types of tears in detail.…”
Section: Operative Techniquesmentioning
confidence: 99%
“…4,16,52,78 The superior strength of vertical sutures is hypothesized to be due to the perpendicular orientation to the circumferential collagen bundles of the meniscus. 52 We have previously described the operative techniques for meniscus repair of various types of tears in detail. 40 Diagnostic arthroscopy is first performed and the meniscus tear analyzed according to its location, type, and size.…”
Section: Operative Techniquesmentioning
confidence: 99%